KREATIVITAS PELAKU USAHA ANYAMAN PURUN STUDI KASUS DI KAMPUNG PURUN KOTA BANJARBARU - Maulida, Inayatul; Agus Ruchliyadi, Dian (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Purun weaving is a distinctive cultural feature of the community in Kampung Purun, Banjarbaru, and has become an integral part of daily life. The issue addressed in this study is the community’s low interest in the local wisdom of purun weaving, a situation that has since improved thanks to the creative contributions of local entrepreneurs in Kampung Purun. The main focus of this study is to examine how the creativity of purun weaving entrepreneurs in Kampung Purun can foster residents’ appreciation for local wisdom. The objective of this study is to identify the factors causing the decline in public interest and the forms of creativity exhibited by purun weaving entrepreneurs in Banjarbaru.